230k views
0 votes
If f(×)=2x^2-5 and g(×)=3×+3 find (f-g)(×)

a.3x-2x^2-2
b.2x^2-3x-2
c.-x^2-7
d.2x^2-3x-8

2 Answers

3 votes
The answer is:

2 {x}^(2) - 5 - 3x - 8 = 2 {x}^(2) - 3x - 8
User Noun
by
5.7k points
4 votes

Answer:

d. 2x^2 -3x -8

Explanation:

if f(×)=2x^2-5 and

g(×)=3×+3

(f-g)(×)=

I like to line them up vertically

2x^2-5

-(3x+3)

-------------------

Distribute the minus sign

2x^2-5

-3x-3

-------------------

Line up the powers


2x^2+ 0x -5

-3x-3

-------------------

2x^2 -3x -8

User Ryan Plant
by
5.5k points